Azospirillum brasilense locus coding for phosphoenolpyruvate:fructose phosphotransferase system and global regulation of carbohydrate metabolism. - Chattopadhyay, S (1993)
Mutants of Azospirillum brasilense unable to grow on fructose include ones affected only on fructose (Fru-) and others impaired on many or all carbohydrates through interference with induction of their specific pathways (Car-). Both types of mutants could be complemented by a cosmid in broad-host-range vector pLAFR1 containing a 27.5-kb genomic insert, Car(-)-complementing activity depending on a 2.2-kb fragment, and Fru(-)-complementing activity depending on an overlapping 9.6-kb fragment.